Flexible Micropillar Electrode Arrays for In Vivo Neural Activity Recordings. Issue 20 (12th April 2019) - Du, Mingde; Guan, Shouliang; Gao, Lei; Lv, Suye; Yang, Siting; Shi, Jidong; Wang, Jinfen; Li, Hongbian; Fang, Ying
Abstract: Flexible electronics that can form tight interfaces with neural tissues hold great promise for improving the diagnosis and treatment of neurological disorders and advancing brain/machine interfaces. Here, the facile fabrication of a novel flexible micropillar electrode array (µPEA) is described based on a biotemplate method. The flexible and compliant µPEA can readily integrate with the soft surface of a rat cerebral cortex. Moreover, the recording sites of the µPEA consist of protruding micropillars with nanoscale surface roughness that ensure tight interfacing and efficient electrical coupling with the nervous system. As a result, the flexible µPEA allows for in vivo multichannel recordings of epileptiform activity with a high signal‐to‐noise ratio of 252 ± 35. The ease of preparation, high flexibility, and biocompatibility make the µPEA an attractive tool for in vivo spatiotemporal mapping of neural activity. Abstract : Flexible micropillar electrode arrays with multiscale hierarchical surface structure are prepared by a biotemplate method. The recording sites with protruding micropillars can form a tight interface with the soft cerebral cortex of the rat brain, which allows for the in vivo multichannel recordings of epileptiform activity with high signal‐to‐noise ratio.